Myth and Archetype in Recollections of Things to Come - Robert K. Anderson (Studies in 20th & 21st Century Literature, 1985)
According to Elena Garro, "the great writer will be the one who presents the Mexican as a universal being." In her novel Recollections of Things to Come she achieves this goal primarily through an incessant infusion of mythic and archetypal motifs, elements that constitute the cornerstone of this study.
Keywords: Elena Garro; Mexican; represent; representation; Recollections of Things to Come; mythic; archetypal; motifs